Aktivitas Enzimatis Eko-Enzim Averrhoa bilimbi L. Di Kabupaten Plaju Sumatera Selatan Dengan Variasi pH - Siti Soleha; Delima Engga maretha; Andi Saputra; Siti Rachmi Indahsari; Binsar Butar Butar; Ahma Adi Suhendra; Maharani Maharani; Harlis Harlis; Hari Kapli (Biota, 2023)
Enzymes are biocatalysts that have many benefits in the industry and the environment. Eco-enzymes are reported to have amylase, lipase, and protease activities. Enzymatic activity is strongly influenced by several factors, one of which is pH. This study aims to determine the optimum enzymatic activity (amylase, lipase and protease) of Averrhoa bilimbi L. fruit eco-enzymes with various pH treatments (5, 6, 7, 8). Enzymatic activity was measured using a spectrophotometric method. Amylase activity assay using starch as a substrate. Casein and para nitrophenol palmitate were used as substrates. Casein was used as a substrate in the protease activity assays. In the lipase activity assays, para nitrophenol palmitate was used as substrate. Data analysis results are presented in graphical and descriptive. Averrhoa bilimbi L. fruit eco-enzyme has a protein concentration of 0.459 mg/ml. The optimum activity of amylase at pH 5 was 11,713.871 U/mg. Optimum activity and protease activity occurred at pH 8 and 6 of 3.667 U/mg and 13,400.77 U/mg, respectively.